Relevansi Konsep Pendidikan Islam TGKH. Muhammad Zainuddin Abdul Madjid di Era Kontemporer - Lalu Gede Muhammad Zainuddin Atsani; Ulyan Nasri (Al-Munawwarah : Jurnal Pendidikan Islam, 2023)
This research aims to examine the relevance of the educational concept of TGKH. Muhammad Zainuddin Abdul Madjid in the contemporary era through the qualitative research approach of library research. The Islamic educational concept passed down by TGKH. Muhammad Zainuddin Abdul Madjid is a product of deep contemplative thought that integrates religious values with the advancements of time. The contemporary era is characterized by rapid social, technological, and informational dynamics, thus necessitating an evaluation of the relevance of the Islamic educational concept. This study employs a library research approach to collect, analyze, and synthesize literature related to the Islamic educational concept of TGKH. Muhammad Zainuddin Abdul Madjid. The collected data is analyzed descriptively and interpretively to identify the elements of the Islamic educational concept and its implications in the contemporary era. The research findings indicate that the Islamic educational concept of TGKH. Muhammad Zainuddin Abdul Madjid holds strong relevance in the contemporary era. This concept emphasizes deep understanding of religious teachings, the establishment of noble ethics, self-development, community empowerment, and the strengthening of faith and piety. This relevance is reflected in the concept's ability to respond to challenges and opportunities emerging in the context of globalization, pluralism, and technology. The Islamic educational concept of TGKH. Muhammad Zainuddin Abdul Madjid also encourages the formation of resilient and tolerant character traits, as well as the ability to adapt to the changing times. This research affirms the significant relevance of the Islamic educational concept inherited from TGKH. Muhammad Zainuddin Abdul Madjid in the contemporary era. This concept can serve as a guide for educational institutions and Muslim communities in facing various challenges and dynamics of the modern age. It is hoped that this research contributes to enriching the discourse on Islamic education amidst the complexity of current global developments.